Skin-to-Skin Contact and Parental Stress among Parents with Preterm Infant during NICU Admission: A Review - Hikmi Muharromah Pratiwi; Desiyani Nani (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2023)
Background: Psychological distress of parents with preterm infant also could be treated appropriately by enhancing parent’s involvement in infant care, including skin-to-skin contact. A few of studies related to skin-to-skin contact have revealed can benefit from infant and parental outcomes. The previous review only explored the distress among parents with healthy infant. The effect skin-to-skin contact among parents with preterm infant is necessary to be investigated. Objective: This article provided a review related to effect of skin-to-skin contact toward parent stress during preterm infant’s hospitalization in NICU. Methods.A literature review was performed by searching of trials using PubMed, Cochrane Library, MEDLINE, and CINAHL and published in English from 2012 to 2022, English-published, full text availability related to skin-to-skin contact, or Kangaroo Mother Care, preterm infants and parental distress (mother and/or father) in NICU. Result: This study involved six trials and 489 parents with preterm infant. Fours studies explored maternal stress and the others assessed parental stress during NICU admission. Five trials reported parental stress deflation after skin-to-skin contact with their infants, otherwise one trial revealed that skin-to-skin contact escalated parental stress due to a more facilitated infant progression. Conclusion: Skin-to-skin contact benefits parents with preterm infants by decreasing the psychological distress during NICU admission.